Strategi Pengembangan Lembaga Pengelolaan Hutan Desa (LPHD) yang Berkelanjutan Untuk Menunjang Kawasan Ekonomi Khusus di Kabupaten Pulau Morotai - Febriyanto I. Piara; Yusri Sapsuha; Hamidin Rasulu; Syamsul Bahri; Andy Kurniawan; Aisjah Rahmawaty Ryadin (Universitas Khairun, 2025)
Morotai Island Regency, located in North Maluku Province, has significant forest resource potential. Forests in this region serve not only as raw material providers but also as ecosystem buffers vital to the livelihoods of local communities. Village Forest Management Institutions (LPHD) are expected to play a key role in sustainable forest resource management to support the development of Special Economic Zones (SEZs). The purpose of this study is to analyze the challenges faced by Village Forest Management Institutions (LPHDs) in Morotai Island Regency and to identify strategies for sustainable development of Village Forest Management Institutions (LPHDs) in Morotai Island Regency. This research method uses a mixed qualitative and quantitative approach. The results indicate that LPHDs in Morotai Island Regency have significant potential to support the Morotai SEZ, both in terms of natural resource management and economic empowerment.